2012
DOI: 10.1371/journal.pone.0041238
|View full text |Cite
|
Sign up to set email alerts
|

NEMO Inhibits Programmed Necrosis in an NFκB-Independent Manner by Restraining RIP1

Abstract: TNF can trigger two opposing responses: cell survival and cell death. TNFR1 activates caspases that orchestrate apoptosis but some cell types switch to a necrotic death when treated with caspase inhibitors. Several genes that are required to orchestrate cell death by programmed necrosis have been identified, such as the kinase RIP1, but very little is known about the inhibitory signals that keep this necrotic cell death pathway in check. We demonstrate that T cells lacking the regulatory subunit of IKK, NFκB e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…In contrast to the general notion that NEMO exerts its effects via NF-B, these findings indicate that TAK1 and NEMO can prevent cell death independent of NF-B, at least of the p65 subunit and its main activator in the canonical pathway, IKK2. Previous work has already shown in vitro that TAK1 and NEMO can prevent TNF-induced cell death without the need for NF-B-mediated gene transcription (O'Donnell et al, 2012;Dondelinger et al, 2013). Our study now provides the first in vivo evidence for this novel function of TAK1 and NEMO in brain endothelial cells.…”
Section: Mechanisms Of Brain Endothelial Cell Death Upon Disruption Osupporting
confidence: 65%
“…In contrast to the general notion that NEMO exerts its effects via NF-B, these findings indicate that TAK1 and NEMO can prevent cell death independent of NF-B, at least of the p65 subunit and its main activator in the canonical pathway, IKK2. Previous work has already shown in vitro that TAK1 and NEMO can prevent TNF-induced cell death without the need for NF-B-mediated gene transcription (O'Donnell et al, 2012;Dondelinger et al, 2013). Our study now provides the first in vivo evidence for this novel function of TAK1 and NEMO in brain endothelial cells.…”
Section: Mechanisms Of Brain Endothelial Cell Death Upon Disruption Osupporting
confidence: 65%
“…As previously described, NEMO-deficient Jurkat cells were sensitive to TNFinduced cell death, with both a caspase-dependent and independent component ( Fig. 2A) (21,23). Reconstitution of these cells with wild-type NEMO reduced cell death, with the residual cell death being almost completely caspase-dependent, whereas loss of function NEMO mutations affecting the first coiled-coil domain (L153R), the C-terminal zinc finger (C417R), or the UBAN domain (E319AE320A) all failed to prevent cell death in response to TNF (Fig.…”
supporting
confidence: 54%
“…40 Interestingly, it was recently reported that NEMO also negatively regulates TNF-mediated RIPK1-dependent apoptosis and necroptosis independently of NF-kB. 43,44 Whether TAK1 and NEMO collaborate in the early NF-kB-independent cell death checkpoint downstream of TNFR1 by regulating RIPK1 kinase activity is an interesting possibility that will deserve future attention.…”
Section: Discussionmentioning
confidence: 99%